DeconstructingOrganizations - Kilduff, Martín (Academy of Management Review, 1993)
This reading of March and Simon's (1958) Organizations illustrates the deconstructive approach to foundational texts. The article deconstructs the positivist agenda formulated in Organizations to show that the text (a) replicates the moves of predecessors it condemns and (b) asserts an ideology of programming that justifies the inevitability of fractionated work. Deconstruction is used not to prevent science, but to open debate to complexities and issues that have been ignored or suppressed.